2018
DOI: 10.2147/jpr.s163975
|View full text |Cite
|
Sign up to set email alerts
|

Epidural dexmedetomidine infusion for perioperative analgesia in patients undergoing abdominal cancer surgery: randomized trial

Abstract: ObjectiveTo assess the postoperative analgesic efficacy of epidural dexmedetomidine added to bupivacaine infusion for patients undergoing major abdominal cancer surgery.MethodsPatients scheduled for major upper abdominal cancer surgery were allocated to group bupivacaine (n =32), in which patients received epidural bupivacaine infusion (6 mL/h bupivacaine 0.1%) for 48 hours postoperatively, or group bupivacaine + dexmedetomidine (n=32), in which patients received epidural dexmedetomidine added to bupivacaine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Patients receiving epidural dexmedetomidine (0.1 µg/kg) as a loading dose and a continuous infusion of 0.15% ropivacaine at 2 ml/h combined with dexmedetomidine (1 µg/kg in 100 ml of 0.15% ropivacaine) following cesarean section under epidural anesthesia reported insufficient analgesia, with a VAS score >3, whether at rest or while coughing, at 12 and 24 h after surgery (8). Sufficient pain relief was attained in patients undergoing abdominal cancer surgery who received a bolus dose of 6 ml of 0.1% bupivacaine plus 0.5 µg/ml dexmedetomidine, followed by a continuous epidural infusion of 6 ml/h of 0.1% bupivacaine plus 0.5 µg/ml dexmedetomidine throughout the surgical period, continued for 48 h post-operatively (28). Zhang and Li (9) reported that the optimal dose of dexmedetomidine is 4 µg in 0.1% ropivacaine (8 ml) as a loading dose, and an hourly infusion dose for epidural labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving epidural dexmedetomidine (0.1 µg/kg) as a loading dose and a continuous infusion of 0.15% ropivacaine at 2 ml/h combined with dexmedetomidine (1 µg/kg in 100 ml of 0.15% ropivacaine) following cesarean section under epidural anesthesia reported insufficient analgesia, with a VAS score >3, whether at rest or while coughing, at 12 and 24 h after surgery (8). Sufficient pain relief was attained in patients undergoing abdominal cancer surgery who received a bolus dose of 6 ml of 0.1% bupivacaine plus 0.5 µg/ml dexmedetomidine, followed by a continuous epidural infusion of 6 ml/h of 0.1% bupivacaine plus 0.5 µg/ml dexmedetomidine throughout the surgical period, continued for 48 h post-operatively (28). Zhang and Li (9) reported that the optimal dose of dexmedetomidine is 4 µg in 0.1% ropivacaine (8 ml) as a loading dose, and an hourly infusion dose for epidural labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the dose of bupivacaine reduces the intensity of postoperative pain, reduces the opiate administration time to first analgesic demand, and decreases the incidence of nausea and vomiting (8). Intrathecal injection of alpha 2 agonists, such as dexmedetomidine, as adjuncts to topical anesthetics, can enhance the effects of anesthetic drugs and reduce their demand (5, 9-11). Dexmedetomidine as an adjunct directly increases the block time through the direct modulating of receptors on motor neurons and posterior horn sensory neurons of the spinal cord or their synapses (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Hetta et al [14] conducted a study that compared continuous infusions (48 hours) of epidural bupivacaine 0.1% versus bupivacaine 0.1% with dexmedetomidine 0.5 μg/ mL in patients undergoing abdominal cancer surgery and concluded that the addition of dexmedetomidine in epidural route significantly reduced the morphine consumption, delayed time to first rescue analgesia, and reduced pain scores during postoperative 48 hours [14]. In another study on 100 patients undergoing lower limb surgery, dexmedetomidine was compared with fentanyl as an epidural adjuvant and showed better hemodynamic stability, prolonged postoperative analgesia, and better sedation levels [15].…”
Section: Discussionmentioning
confidence: 99%